Theta and Alpha Oscillations during the Retention Period of Working Memory by rTMS Stimulating the Parietal Lobe - Li, Song; Jin, Jing-Na; Wang, Xin; Qi, Hong-Zhi; Liu, Zhi-Peng; Yin, Tao (Frontiers in Behavioral Neuroscience, 2017)
Studies on repetitive transcranial magnetic stimulation (rTMS) have shown that stimulating the parietal lobe, which plays a role in memory storage, can enhance performance during the ‘retention’ process of working memory (WM). However, the mechanism of rTMS effect during this phase is still unclear. In this study, we stimulated the superior parietal lobe (SPL) using 5-Hz rTMS in 26 participants and recorded electroencephalography (EEG) while they performed a delayed-recognition WM task. The analyses included the comparisons of event-related spectral perturbation(ERSP) value variations in theta (4–7Hz) and alpha (8–14Hz) band frequencies between conditions (rTMS versus sham), as well as the correlations between different brain areas. Following rTMS, the ERSP values of theta-band oscillations were significantly increased in the parietal and occipital-parietal brain areas (P < 0.05*), whereas the ERSP values of alpha-band oscillations were significantly decreased in the parietal area (P < 0.05*). The ERSP value variations of theta-band oscillations between the two conditions in the left parietal and left prefrontal areas were positively correlated with the response time (RT) variations (by using rTMS, the more subject RT decreased, the more ERSP value of theta oscillation increased). The ERSP value variations of alpha-band oscillations in the left parietal and bilateral prefrontal areas were negatively correlated with RT variations (by using rTMS, the more RT of the subject decreased, the more ERSP value of alpha oscillation decreased). Inter-sites phase synchronization of theta-band EEG between the left parietal and left prefrontal areas, as well as alpha-band EEG between the left parietal and bilateral prefrontal areas were enhanced by rTMS. These results indicated that activities of both parietal and prefrontal areas were required for information storage, and these activities were related to the behavioral responses. Moreover, the connectivity between these two regions was intensified following rTMS. Thus, rTMS may affect the frontal area indirectly via the frontal parietal pathway.